Molecular characterization of the genomic regions of the Drosophila -type subunit proteasome genes PROS-Dm28.1 and PROS-Dm35. - Frentzel, S.; Troxell, M.; Haass, C.; Pesold-Hurt, B.; Glatzer, K.H.; Kloetzel, P.M. (European Journal of Biochemistry, 1992)
The proteasome (multicatalytic proteinase) consists of a large number of non-identical protein subunits which are encoded by the evolutionarily conserved PROS gene family. Using the PROS-Dm35 and PROS-Dm28.1 cDNAs as probes, we have isolated the corresponding genomic DNA clones of Drosophila melanogaster. In situ hybridization shows that the members of the PROS gene family are not organized in a single gene cluster and that, in contrast to the PROS-Dm35 gene, the PROS-Dm28.1 gene is localized on the X chromosome. Analysis of the genomic organization of the PROS-Dm28.1 and PROS-Dm35 genes reveals that both genes are interrupted by two small introns whereby the relative positions of the introns within the two coding regions are not conserved. Neither gene possesses a distinct transcriptional start site as shown by nuclease S1 analysis. Since the promoter regions also do not contain a TATA box, PROS genes appear to be typical house-keeping genes. A putative heat-shock element in the promoter region of the PROS-Dm35 gene was shown to be inactive on stress induction when fused to a reporter gene and tested in transient transfections assays. In addition, promoter deletion analysis demonstrates that the promoter region between positions -605 and -330 contains sequence elements important for PROS-Dm35 gene activity and that deletions beyond position -150 result in an almost complete inhibition of transcription.